Avaliação neutrônica da inserção de transurânicos em reatores nucleares tipo VHTR - Fabiano Cardoso da Silva (2012)
A neutronic analysis of the behavior of High Temperature Reactors was carried out in this study to investigate the viability of using reprocessed fuel containing transuranic elements, in the concept of fourth-generation reactors. The idea was to evaluate the maximum insertion of transuranic elements to achieve conditions with high transmutation rate of recycled material in the fuel. Initially two High Temperature Reactors (VHTR and LS-VHTR) were modeled for a preliminary analysis of their application using fuel with plutonium and uranium mixed oxides using data available in the literature. For comparison purposes, this study was carried out using two percentages of fissile material insertion (15% and 20%) in reprocessed fuel with UREX + method and diluted with depleted uranium. The results obtained for the VHTR proved to be better. In this way, we continued the next phases of the study with the VHTR reactor, limiting the amount of fissile material at 15%. In the second phase, we evaluated three different percentages of insertion of transuranic elements in the fuel. Neutronic parameters assessed were suitable for all cases, allowing starting the third stage of the study, considering the maximum value of transuranic elements insertion. In the last step, we evaluated two fuels: a fuel diluted in depleted uranium and another in an unprecedented way in VHTR reactors, in natural thorium. The percentage of fissile material was maintained at 15%. The VM/VF core rate was then varied, obtaining a curve as a function of keff and studies have been conducted around the peak, in order to obtain the most appropriate transmutation percentage. The study was conducted using the code WIMSD5 and qualitative analysis of simulations showed a core neutronically well-behaved, demonstrating the possibility of using reprocessed fuel and good transmutation reason for both fuels.